Planning for protraction a historically informed approach to great-power war and Sino-US competition - Rehman, Iskander (The Adelphi series, 2023)
As Sino-US relations have deteriorated, concerns have grown in Washington over its ability to defeat China in a major conflict. A conflict between such peer competitors would likely become a protracted war of attrition drawing on all dimensions of national power, but this reality has yet to receive a sufficient degree of analytical attention. In this Adelphi book, Iskander Rehman provides a historically informed and empirically grounded study of protracted great-power war, its core drivers and characteristics, and an examination of the elements that have most often determined a competitor's long-term strategic performance. Final victory in a protracted conflict, this book argues, rests on a combination of three core factors: a state's military effectiveness and adaptability, its socio-economic power and resiliency, and the soundness of its alliance management and grand strategy. A detailed analysis of the contemporary Sino-US rivalry assesses how both parties might fare in the event of a protracted war, while highlighting some of its key differentiating aspects - most notably its nuclear and cyber dimensions.